SIKAP, NORMA SUBJEKTIF DAN KONTROL PERILAKU PADA IMPLEMENTASI KESELAMATAN KERJA : DAMPAKNYA TERHADAP INTENTION TO COMPLY (Studi Pada Pekerja Kontraktor PT. Hutama Karya Kantor Wilayah IV Bali, NTB, NTT) - Oka Hartoni, I Gusti Putu; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
The purpose of this study was to analyze the influence of worker attitudes, subjective norms and behavioral control toward Intention to Comply on the policy of implementation Occupational Health, Safety and Environment (K3L). Respondents in this study were all employees and construction workers on the project Watermark Hotel & Spa Bali at Jalan Raya Uluwatu, Jimbaran, Bali, filmed contractor PT. Hutama Regional Office IV Bali, NTB, and NTT. The sampling technique used was purposive sampling technique, researcher have consideration, that the workers who made the respondents are the workers whose jobs are directly related to the operational activities in the field of this project. The respondents amounted to 105 people. The research instrument used questionnaires and analysis techniques used were multiple linear regression analysis. The results showed that the attitude of the workers in the implementation of safety policies in a positive and significant effect on Intention to Comply, subjective norm, and a significant positive effect on Intention to Comply, and control the behavior of workers and significant positive effect on Intention to Comply. Implications of research namely, the theory of planned behavior (TPB) is determined by beliefs held by individuals, depending on the knowledge and control of the control that. Control control factors consist of internal and external. TPB only focus on individual psychological determinants. Attitudes may also be influenced by demographic factors. Thus, it becomes a very important factor to be considered in future research. Not all research topics can be implemented and tested by TPB, associated with different problems.
Keywords: Attitudes, Subjective Norms, Control Behavior, Intention to Comply